Molecular Identification of Anopheles (Diptera: Culicidae) Species in Native Communities of a Northeastern Region of Peru - Eddyson Montalvo-Sabino; Marianella Villegas-Pingo; Jhon Zumaeta; Lizandro Gonzales; Rafael Tapia-Limonchi; Marta Moreno; Christian R. González; Stella M. Chenet (Microorganisms)
Background: Malaria is a severe health problem in native communities of Condorcanqui in the Amazonas region of Peru. Recently, the number of malaria cases has increased considerably following a Plasmodium falciparum outbreak in 2019. However, there is no information on the anophelines acting as Plasmodium vectors in this area. This study aimed to identify Anopheles species circulating in previously unexplored native communities of Condorcanqui. Additionally, we sought to detect the presence of DNA from P. vivax and P. falciparum parasites in mosquitoes. Methods: During three exploratory visits between March and September 2022, 453 mosquitoes were collected using Shannon traps and CDC light traps. Only specimens morphologically identified as Anopheles sp. were subjected to molecular confirmation through PCR amplification and sequencing of the Cox1 barcode region. Plasmodium parasites were detected using nested PCR targeting of the 18S rRNA subunit, while human blood meal feeding was evaluated using a human β-globin marker. Results: A total of 66 specimens were molecularly confirmed as anopheline species: An. benarrochi B, An. triannulatus, An. Costai, and An. nimbus. Six specimens of An. benarrochi B were exclusively positive for Plasmodium parasites by PCR. Moreover, four specimens tested positive for Plasmodium and the presence of human blood, suggesting the anthropophilic behavior of An. benarrochi B and its possible role as a potential malaria vector in this area. Conclusions: In conclusion, while this study provides valuable insights into the potential role of Anopheles benarrochi as a malaria vector in Amazonas, further research is essential to fully understand its behavior and transmission dynamics in the region.